Elucidation of association for yield attributing traits in country bean (Progressive Agriculture, 2017)
Twenty genotypes of country bean were evaluated to explore the association between yield and yield contributing traits in country bean in field condition. Experiment was conducted at field laboratory of department of Genetics and Plant Breeding (GPB), Bangladesh Agricultural University (BAU), Mymensingh. Traits association through computing correlation coefficient and path coefficients were done both at genotypic and phenotypic levels. Among the twelve morphological  traits, genotypic and phenotypic correlation studies showed number of raceme per plant and number of flower buds per raceme had significantly positive relationship with seed yield per plant. Genotypic correlation also showed significant positive relation between number of seed per plant and seed yield per plant. Path coefficient analysis revealed that days to 50 per cent flowering, number of raceme per plant, green pod length, 100 dry seed weight, green shelling percentage, dry shelling percentage showed positive effect on seed yield in genotypic level . Also in phenotypic level days to 50% flowering, days to maturity, number of flower buds per plant, green pod length, number of seed per pod, green pod yield per plant, green test weight and dry shelling percentage showed direct effect on seed yield. The association between traits revealed in the present study shall be of great help to choose parents with desirable traits for hybridization, selection method to follow, and selection criteria towards a successful breeding program. Traits with strong association with yield can be improved easily, but with weak relationship, needs more observations to obtain the better segregates.Progressive Agriculture 28 (3): 184-189, 2017